METODE NEW JERSEY UNTUK CADANGAN ASURANSI JIWA DWIGUNA DENGAN DISTRIBUSI GOMPERTZ - Ramlah Annuri; Tumpal P. Nababan; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This  article  discusses  the  prospective premium  reserve modified  using  New  Jersey method on endowment insurance.  This method limits  calculation of reserves for 20 years. The calculations of the endowment insurance reserve is solved  by  priordetermination  of the annuity, single premium, and annual premium based on the  distribution of Gompertz.